Kajian konsentrasi pupuk hayati dan 3 macam pupuk kandang terhadap pertumbuhan dan hasil bawang merah (Allium ascalonicum L.): Konsentrasi, Pupuk Hayati, Pupuk Kandang, Bawang Merah - Maulani, Rizki; Santosa, Sartono Joko; Triyono, Kharis (innofarm, 2024)
Research "Study of the Concentration of Biological Fertilizers and 3 Types of Manure on the Growth and Yield of Shallots (Allium ascolonium L.)". The aim is to examine the best concentration of biological fertilizer and the dosage of 3 types of manure on the growth and yield of shallots. This research was carried out from January 13 2024 to March 17 2024 at the Tohudan Horticultural Seed Garden, Colomadu District, Karanganyar Regency. The method used in this research was a Complete Randomized Block Design (CRBD) which consisted 0f 2 treatment factors and 3 replication. The first factor is the concentration of biological fertilizer which consists of 4 levels, namely K0 = No biological fertilizer, K1 = 7,5ml/liter, K2 = 15 ml/liter and K3 = 22,5 ml/liter with the second factor 3 types of manure consisting of the 4 levels, namely M0 = No manure, M1 = Goat mqanure 10 tons/ha, M2 = Cow manure 20 tons/ha and M3 = Chicken manure 10 tons/ha. 1). The treatment of giving biological fertilizer concentration had very significant differences in the parameters height of plant, number of leaves, weight of wet stover, weight of dry strover and for yield parameters were weight of wet bulb, weight of dry bulb, number of bulb and height of blub. 2). The treatment of manure dosage has very significant differences in terms of parameters height of plant, number of leaves, weight of wet stover, weight of dry strover and for yield parameters were weight of wet bulb, weight of dry bulb, number of bulb and height of blub. 3). The interaction between different treatments is very significant for all observed parameters, namely height of plant, number of leaves, weight of wet stover, weight of dry strover and for yield parameters were weight of wet bulb, weight of dry bulb, number of bulb and height of blub. 4). A biological fertilizer concentration of 22,5 ml/liter with chicken manure 10 tons/ha gave the best results for weight of wet bulb parameters with an avarge value of 115 grams and weight of dry bulb of 109 grams. The observation data will be subjected to Analysis Of Variance (ANNOVA) if the differences are significant, followed by the Duncan Test with a level of 5%.